Recalibrating a doctor’s duty to advise - LOW, Kee Yang (Institutional Knowledge at Singapore Management University, 2020)
Section 37 of the Civil Law ActThe past two decades have witnessed significant developments in the area of a doctor’s duty to advise his patient. Whilst observers are still digesting the full implications of the Hii Chii Kok modifications to the Montgomery test, the legal position has been altered yet again, this time by the statutory addition of s 37 of the Civil Law Act. This article examines the changes and their implications.